The Effect of Global Challenge, Managerial Challenge and Environmental Challenge to Increase Competitiveness and Human Resource Performance - Sulhan Manaf (Pusat Publikasi Nusantara, 2022)
Globalization has a major influence on the order of human life, so that society has its own challenges, including competitiveness and the performance of human resources which are then exacerbated by the Covid-19 pandemic. This study aims to determine the effect of global challenges, managerial challenges and environmental challenges to increase competitiveness and human resource performance in the Covid-19 era. This study uses a quantitative research method with a descriptive approach. The data collection technique in this study used a questionnaire in the form of Google Docs which was distributed to several social media platforms as well as by exploring journals, books and other information relevant to the study. The results of the study show that global challenges, managerial challenges and environmental challenges partially and simultaneously have a significant effect on increasing the competitiveness and performance of human resources. The results showed that global challenges and environmental challenges partially and simultaneously had a significant effect on increasing competitiveness, while managerial challenges did not have a partial significant effect but simultaneously had a significant effect. Then the variable test results of global challenges, managerial challenges and environmental challenges partially and simultaneously have a significant effect on improving human resource performance.